An FSH and TSH pituitary adenoma, presenting with precocious puberty and central hyperthyroidism. (7th July 2017) - Vargas, Guadalupe; Balcazar-Hernandez, Lourdes-Josefina; Melgar, Virgilio; Magriña-Mercado, Roser-Montserrat; Gonzalez, Baldomero; Baquera, Javier; Mercado, Moisés
Abstract : A 19-year-old woman with a history of isosexual precocious puberty and bilateral oophorectomy at age 10 years because of giant ovarian cysts, presents with headaches and mild symptoms and signs of hyperthyroidism. Hormonal evaluation revealed elevated FSH and LH levels in the postmenopausal range and free hyperthyroxinemia with an inappropriately normal TSH. Pituitary MRI showed a 2-cm macroadenoma with suprasellar extension. She underwent successful surgical resection of the pituitary tumor, which proved to be composed of two distinct populations of cells, each of them strongly immunoreactive for FSH and TSH, respectively. This mixed adenoma resulted in two different hormonal hypersecretion syndromes: the first one during childhood and consisting of central precocious puberty and ovarian hyperstimulation due to the excessive secretion of biologically active FSH and which was not investigated in detail and 10 years later, central hyperthyroidism due to inappropriate secretion of biologically active TSH. Although infrequent, two cases of isosexual central precocious puberty in girls due to biologically active FSH secreted by a pituitary adenoma have been previously reported in the literature. However, this is the first reported case of a mixed adenoma capable of secreting both, biologically active FSH and TSH. Learning points: Although functioning gonadotrophinomas are infrequent, they should be included in the differential diagnosis of isosexual central precocious puberty. Some functioning gonadotrophinomas are mixed adenomas, secreting other biologically active hormones besides FSH, such as TSH. Early recognition and appropriate treatment of these tumors by transsphenoidal surgery is crucial in order to avoid unnecessary therapeutic interventions that may irreversibly compromise gonadal function.